The Study of Micro-Pressure Inner-Loop Bioreactor Oxygen Mass Transfer Characteristics. (March 2018) - Wan, L G; Lin, Q; Bian, D J; Ren, Q K; Xiao, Y B; Lu, W X
Abstract: The oxygen mass transfer characteristics in a Micro-Pressure Inner-Loop bioreactor (MPR) were studied by clean water oxygenation experiment, the results show that when the aeration adopt by 0.1, 0.2, 0.4, 0.6 m 3 ·h - 1, respectively, the oxygen mass transfer coefficient KLa(20) in the reactor increases with the increase of the aeration. KLa(20) shows a good linear correlation with the aeration. The rate is 0.2128 h·m - 3·min - 1 and the correlation coefficient R=0.993. However, the trend of EO2 increases first and then decreases with the increase of aeration. When the aeration increased to 0.4 m 3 ·h - 1, the EO2 reaches the maximum. If aeration increases constantly, EO2 begin to decrease excessive aeration may lead to an increase in energy waste during reactor operation.